Over a million students use our free study notes to help them with their homework
I would use the fact that ln is the inverse function of the exponential function e^x to re-write the equation as x=e^y. This can be directly seen by just putting e^y=e^(lnx). Since the definition of a ln(...
First, use the identity cos(2x)=(cos(x))^2-(sin(x))^2 along with the identity (sin(x))^2+(cos(x))^2=1 to obtain the integral of 1/2*(1-cos(2x)) as it is not possible to integrate (sin(x))^2 straight off w...
Here we have two equations with two unknowns, the method we use to solve this is substitution. First, find one of the unknowns in terms of the other by rearranging the first equation to arrive at y = 3x -...
Rearrange the second equation in terms of y: meaning that the equation is of the form y = ....-this will give y = 3 - x/2You may now substitute the y in the left hand equation with what y in the right han...
←
594
595
596
597
598
→
Internet Safety
Payment Security
Cyber
Essentials